(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Tuberculosis, a common infection which affected 19 to 43 % of the world population due to the increase of the incidence and development of severe forms, is an international and national problem not only in the developing but also economically developed countries of the world. Purpose. To investigate changes in the clinical picture of tuberculosis eye affection (pathomorphosis) for the period of 1964—1985 and 2000 to 2009. Material and methods. Retrospective analysis of medical records of outpatient and hospitalized patients with tuberculosis affection of the eye. Results. Analysis of clinical changes and the incidence of various forms of tuberculosis eye affection (pathomorphosis) for the period of 1964—1985 and 2000 to 2009. Frequency of tuberculosis chorioretinites in the toxic-allergic process (primary and chronic) increased from 15.7—16.0 to 20.2—27.3 % of cases. Conclusions. In primary chronic toxic-allergic process the number of episcleritis and keratitis decreased from 25.2—26.9 % (in 1964—1985) to 7.0—17.1 % (2000-2009), while the number of iridocyclitis increased from 7.02—8.9 % to 9.3—18.8 % respectively. In primary and metastatic chronic tuberculosis the amount of episcleritis, sclerites and keratitis decreased from 29.8—38.6 % to 4.3—8.7 %, while the number of iridocyclitis increased from 12.1 % to 4.7—6.9—13.9 %. Tuberculosis chorioretinites in primary and metastatic chronic tuberculosis inflammation occurs much more often — 26.0—34.7 % compared with 6.6—13.0 % in recent years.